Genetic linkage to the type VII collagen gene (COL7A1) in 26 families with generalised recessive dystrophic epidermolysis bullosa and anchoring fibril abnormalities. Issue 10 (October 1994) - Dunnill, M G; Richards, A J; Milana, G; Mollica, F; Atherton, D; Winship, I; Farrall, M; al-Imara, L; Eady, R A; Pope, F M
Abstract : To strengthen the evidence for genetic linkage to COL7A1, we have studied 26 generalised recessive dystrophic epidermolysis bullosa (EB) families of British, Italian, Irish, and South African origin. We chose two linkage markers, a COL7A1 PvuII intragenic polymorphism and a highly informative anonymous microsatellite marker, D3S1100, which maps close to the COL7A1 locus at 3p21.1-3. Diagnosis was established by family history, clinical examination, immunofluorescence, and ultrastructural studies. The PvuII marker was informative in 16 families with a maximum lod score (Zmax) of 3.51 at recombination fraction (theta) = 0. The D3S1100 microsatellite was informative in 24 out of 25 families with Zmax = 6.8 at theta = 0.05 (Z = 4.94 at theta = 0) and no obligatory recombination events. These data strongly suggest that COL7A1 mutations cause EB in these families and, combined with previous studies, indicate locus homogeneity. The importance of anchoring fibrils for dermal-epidermal adhesion is further underlined. D3S1100 may later prove useful in prenatal diagnosis of this disease, if used in combination with other markers.